Answer: part a.) c =2A/d
Part b.) d = 7
Part C The diagonals are each 8
Step-by-step explanation: part b:
35= 10d/2 70= 10d. 7 =d
Part c 32= 2c²
64 = c²
√64 = √c²
c = 8
H = 3b+2
A = (h*b)/2 28 = (3b+2)b/2 56 = 3b²+2b 0 = 3b² + 2b - 56
⊕
![\left \{ {{y=2} \atop {x=2}} \right. \int\limits^a_b {x} \, dx \lim_{n \to \infty} a_n \left[\begin{array}{ccc}1&2&3\\4&5&6\\7&8&9\end{array}\right] \beta \\ \\ \\ x^{2} \sqrt{x} \sqrt[n]{x} \frac{x}{y} x_{123} x^{123} \leq \geq \pi \alpha \left[\begin{array}{ccc}1&2&3\\4&5&6\\7&8&9\end{array}\right] \left[\begin{array}{ccc}1&2&3\\4&5&6\\7&8&9\end{array}\right] x_{123} \int\limits^a_b {x} \, dx \left \{ {{y=2} \atop {x=2}}](https://tex.z-dn.net/?f=%20%5Cleft%20%5C%7B%20%7B%7By%3D2%7D%20%5Catop%20%7Bx%3D2%7D%7D%20%5Cright.%20%20%5Cint%5Climits%5Ea_b%20%7Bx%7D%20%5C%2C%20dx%20%20%5Clim_%7Bn%20%5Cto%20%5Cinfty%7D%20a_n%20%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%263%5C%5C4%265%266%5C%5C7%268%269%5Cend%7Barray%7D%5Cright%5D%20%20%5Cbeta%20%20%5C%5C%20%20%5C%5C%20%20%5C%5C%20%20x%5E%7B2%7D%20%20%5Csqrt%7Bx%7D%20%20%5Csqrt%5Bn%5D%7Bx%7D%20%20%5Cfrac%7Bx%7D%7By%7D%20%20x_%7B123%7D%20%20x%5E%7B123%7D%20%20%5Cleq%20%20%5Cgeq%20%20%5Cpi%20%20%5Calpha%20%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%263%5C%5C4%265%266%5C%5C7%268%269%5Cend%7Barray%7D%5Cright%5D%20%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%263%5C%5C4%265%266%5C%5C7%268%269%5Cend%7Barray%7D%5Cright%5D%20%20x_%7B123%7D%20%20%5Cint%5Climits%5Ea_b%20%7Bx%7D%20%5C%2C%20dx%20%20%5Cleft%20%5C%7B%20%7B%7By%3D2%7D%20%5Catop%20%7Bx%3D2%7D%7D)
ω
l
∩
I believe it is 48.
0+3=3
3+5=8
8+7=15
15+9=24
24+11=35
35+13=48
Answer:
Sam gets £30 and Bethan gets £24.
Why?
When dealing with ratios, add up the numbers in the ratio.
5 + 4 = 9
Now, divide the total amount of money by that number.
£54/9 = 6
Now you have the base rate. Multiply each quantity in the ratio by this number.
5*6 = 30
4*6 = 24
Now, the ratio is (in euro) 30:24. This means that Sam has £30 and Bethan has £24.
Check:
30 + 24 = 54
The answer is c.
I will explain
p - 2r = q
1. Move variable to the right by adding it’s opposites on both sides
p - 2r + 2r = q + 2r
2. Eliminate the opposites (-2r and +2r)
p = q + 2r